Implementation of Serang Mayor Regulation Number 36 of 2018 About Guidelines for Utilizing Information and Communication Technology in Local Government Administration Through the RAGEM Application at the Serang City Communication and Informatics Office - Riska Amelia; Try Adhi Bangsawan; Dede Qodrat Al-Wajir (Journal of Innovative and Creativity (Joecy), 2026)
This research is motivated by the less-than-optimal implementation of Serang Mayor Regulation Number 36 of 2018 concerning Guidelines for the Utilization of Information and Communication Technology in the Administration of Local Government through the RAGEM application at the Serang City Communication and Informatics Office. The problems faced include limited information transparency, low public participation, suboptimal responsiveness and coordination among Regional Apparatus Organizations (OPD), as well as technical obstacles and resource limitations that affect the effectiveness of digital-based public services. This study aims to analyze the implementation of that policy, community participation, responsiveness and coordination between OPDs, as well as the challenges faced in managing the RAGEM application. The research used a qualitative method with a case study approach. Data was collected through observation, interviews, and documentation, and then analyzed using George C. Edward III's policy implementation theory, which includes communication, resources, disposition, and bureaucratic structure. The research results show that the implementation of the RAGEM application has generally been going quite well. Aspects like communication, resources, disposition, and bureaucratic structure have supported policy implementation, but it's not yet optimal because public outreach is still limited, human resources and infrastructure capacity are inadequate, complaint response is still low, and coordination and bureaucratic flow between departments still need improvement. Even so, the RAGEM app has been contributing to supporting digital-based public services and complaints in Serang City. Therefore, it is necessary to strengthen socialization, improve human resource capacity, develop information technology infrastructure, and optimize coordination between OPDs to enhance the quality of public services that are effective, responsive, transparent, and accountable.